Instalasi Teknologi Hidroponik sebagai Upaya Pemberdayaan Masyarakat Desa Sukodono dalam Meningkatkan Kemandirian Pangan : Pengabdian - Pradiza, Revvan Rifada; Siswantoro, Dwi Heru; Apriandy, Kevin Ilham; Asrofi, Mochamad; Dwilaksana, Dedi; Sutjahjono, Hary; Yani, Luluk Fitri (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This community service activity aims to improve the understanding and skills of residents of RT 07, Sukodono Village, Sidoarjo, in applying hydroponic technology as a solution for managing limited land and supporting food security. This activity consists of lectures and discussions, as well as the installation of a hydroponic system. During the lectures and discussions, residents were given an understanding of the basic principles of hydroponics, its benefits, and how to apply it in limited land. Discussions were held to explore more deeply the challenges and potential of applying hydroponics in a household environment. The final stage, the installation of the hydroponic system, involved residents directly in the creation and installation of a simple but effective hydroponic system. Although there was no harvest to report at the time of the activity, residents successfully understood and installed the hydroponic system correctly. This success shows that residents of RT 07, Sukodono Village have the potential to manage hydroponic gardens independently. This activity made a significant contribution to increasing food self-sufficiency at the local level, even though challenges in terms of maintenance and limited resources remain.